The role of reiki in the prevention of burnout syndrome among healthcare workers - Stankovic, Veroslava; Jovic, Dragana (Education and Research in Health Sciences, 2026)
Burnout syndrome represents a significant challenge in contemporary work environment, particularly within healthcare and helping professions characterized by high levels of emotional involvement, responsibility, and chronic exposure to stress. According to the World Health Organization, burnout is defined as an occupational phenomenon resulting from chronic workplace stress that has not been successfully managed and is manifested through emotional exhaustion, depersonalization, and a reduced sense of professional efficacy. Given the limitations of conventional preventive approaches alone, increasing attention has been directed toward integrative and complementary interventions targeting psychophysiological stress regulation. The aim of this review paper was to examine, based on an analysis of the available scientific literature, the role of Reiki as a complementary therapeutic method in the prevention of burnout syndrome among healthcare and helping professionals. The paper is based on a comprehensive review of relevant international and national studies published between 2000 and 2025, with a qualitative synthesis of theoretical models of burnout, the principles of Reiki practice, and empirical findings regarding its effects. The results of the literature review indicate that Reiki may contribute to reductions in perceived stress, emotional exhaustion, and anxiety, as well as improvements in subjective well-being and professional functioning. Several studies also report favourable changes in physiological stress markers, including heart rate variability, cortisol levels, and immune parameters. Although methodological limitations are present in the existing research, the consistency of findings suggests that Reiki may play a meaningful role as an adjunctive strategy within integrative programs aimed at preventing burnout syndrome.